A new prognostic model using the NCCN-IPI and neutrophil-to-lymphocyte ratio in diffuse large B-cell lymphoma. Issue 4 (August 2018) - Go, Se-Il; Park, Sungwoo; Kim, Jung Hoon; Kim, Hye Ree; Kim, Minyoung; Moon, Kyunglan; Seo, Jangho; Lee, Gyeong-Won
Background: The neutrophil-to-lymphocyte ratio (NLR) has been known to predict the prognosis in diffuse large B-cell lymphoma (DLBCL). We planned to design a new prognostic model in DLBCL using well-known prognostic index and NLR. Methods: The data of 232 DLBCL patients treated with first-line R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) from 2004 to 2017 were retrospectively reviewed. Patients with NLR ≥6 and <6 were determined as the high and low NLR groups, respectively. Treatment response and survival were compared according to NLR status. Nomograms for predicting 5-year progression-free survival (PFS) and overall survival (OS) rates were constructed using NLR and other prognostic factors based on the National Comprehensive Cancer Network-International Prognostic Index (NCCN-IPI) NCCN-IPI. Results: The high NLR group had a low complete response (CR) rate compared to low NLR group (51.6% vs. 83.5%; p<0.001). The 5-year PFS and OS rates were 27.4% and 30% in the high NLR group and 61.1% and 63.7% in the low NLR group, respectively (both p<0.001). Multivariate analyses confirmed that NLR is one of the independent risk factors for failure to achieve CR and for worse PFS and OS. The nomogram showed superior discrimination ability for predicting 5-year PFS and OS rates compared with NCCN-IPI (c index 0.78 vs. 0.75 and 0.79 vs. 0.75, respectively). Conclusions: High NLR was associated with poor treatment response and worse PFS and OS in DLBCL. The nomogram developed from NCCN-IPI-based variables and NLR may help the clinicians to predict the prognosis individually in DLBCL patients, although it needs to be validated in the independent cohort.